Relationship of cause and effect between depression and night eating syndrome as predictor of abdominal obesity - I. S. Dzheriyeva; N. I. Volkova; S. I. Rapoport (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Assessment of frequency of night eating syndrome (NES) at presence of depression (D) in men with obesity and diagnostics of initial cause of eating disorders (ED).Material and methods. Overall 38 ьфдуы aged 47±4 years, BMI 38±3 kg /m2 were investigated. CES-D scale was used for D diagnostics. NES was registered according to A. Stunkard criteria. Statistical analysis was carried out by Statistica 8.0 software.Results. NES with D was diagnosed in 64% of cases, without D – in 25% of cases. In the main group the risk of its development was significantly higher, than in control group – OR=1,75 (95% CI=1,2–3,7).Conclusions. In patients with D and obesity NES was significantly more frequent, than in patients without affective disorders. The risk of ED development in patients with D is significantly higher, than in patients without D.